INFORMAREA ÎN PROCESUL DE INOVARE - USM ADMIN (Moldova State University, 2009)
The article presents aspects related to the use of the innovation process. First of all, it is necessary to inform each individual about the role of information to the teaching staff, young researchers, etc. The analysis is made of literature related to the topic, also it is proposed to form an innovation bank for the teaching staff.